RIFM fragrance ingredient safety assessment, 1-(5, 5-dimethyl-1-cyclohexen-1-yl)pent-4-en-1-one, CAS Registry Number 56973-85-4. (15th April 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Highlights: 1-(5, 5-Dimethyl-1-cyclohexen-1-yl)pent-4-en-1-one; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.